Late onset infectious complications and safety of tocilizumab in the management of COVID‐19. Issue 3 (21st August 2020) - Pettit, Natasha N.; Nguyen, Cynthia T.; Mutlu, Gökhan M.; Wu, David; Kimmig, Lucas; Pitrak, David; Pursell, Kenneth
Abstract: Background: Tocilizumab (TCZ) has been used in the management of COVID‐19‐related cytokine release syndrome (CRS). Concerns exist regarding the risk of infections and drug‐related toxicities. We sought to evaluate the incidence of these TCZ complications among COVID‐19 patients. Methods: All adult inpatients with COVID‐19 between 1 March and 25 April 2020 that received TCZ were included. We compared the rate of late‐onset infections (>48 hours following admission) to a control group matched according to intensive care unit admission and mechanical ventilation requirement. Post‐TCZ toxicities evaluated included: elevated liver function tests (LFTs), GI perforation, diverticulitis, neutropenia, hypertension, allergic reactions, and infusion‐related reactions. Results: Seventy‐four patients were included in each group. Seventeen infections in the TCZ group (23%) and 6 (8%) infections in the control group occurred >48 hours after admission ( P  = .013). Most infections were bacterial with pneumonia being the most common manifestation. Among patients receiving TCZ, LFT elevations were observed in 51%, neutropenia in 1.4%, and hypertension in 8%. The mortality rate among those that received TCZ was greater than the control (39% versus 23%, P  = .03). Conclusion: Late onset infections were significantly more common among those receiving TCZ. Combining infections and TCZ‐related toxicities, 61% of patients had a possible post‐TCZ complication. While awaiting clinical trial results to establish the efficacy of TCZ for COVID‐19 related CRS, the potential for infections and TCZ related toxicities should be carefully weighed when considering use. Highlights: Infectious complications and drug‐related toxicities are concerns associated with TCZ use. Among COVID‐19 patients presenting with a hyper‐inflammatory response receiving TCZ, 61% had a possible post‐TCZ complication. Additional studies are needed to further evaluate the safety and efficacy of TCZ in the management of patients with COVID‐19.